Examination of Fourth-Grade Students’ Mental Structures Regarding Natural Disasters - Elif Bayer Kurt; Özlem Özçakır Sümen (Sakarya University Journal of Education)
Providing students with knowledge and awareness from an early age in natural disaster education is important. This research examines the mental structures of fourth-grade primary school students about natural disasters. The model of the study is a case study, one of the qualitative research methods. The participants were 14 students studying in the fourth grade at a public school in Terme, Samsun. The study group was determined by convenience sampling. Mind maps and semi-structured interview forms were used as data collection tools. The data were analyzed using the content analysis and descriptive analysis methods. As a result of the research, it was revealed that students’ mental structures regarding natural disasters were grouped under 13 themes: earthquakes, floods, erosion, landslides, fire, avalanches, tornadoes, tsunamis, volcanic eruption, hurricanes, storms, lightning, and thunder. In addition, many different codes were obtained under the sub-themes of the causes of the natural disaster, its consequences, precautions, and what to do during a natural disaster. These codes revealed that the students had rich mental structures regarding natural disasters. However, it was also determined that they confused some climate events with natural disasters. The interviews supported the idea that the students had sufficient knowledge about natural disasters and the precautions. Updating textbooks on this subject and including more activities to attract children’s attention in lessons will ensure that primary school students receive a better education on natural disasters and become more equipped.